O imaginário e a estética do cinema na formação de professores da educação de jovens e adultos da escola Dr. Romário Araújo de Oliveira - Amaral, Paulo César Fagundes do (2019)
The research was developed in the Master's Course in Education of the Graduate Program in Education at the Federal University of Santa Maria, integrating Line of Research of Teaching, Knowledge and Professional Development. The objective focused on understanding the repertoire and the imaginary of teachers in the language of Brazilian cinema and its use in the Youth and Adult Education classes, at Dr. Romário Araújo de Oliveira School, in Alegrete city. Firstly, the theoretical foundations were shared to situate educators according to the context of the proposal in which the study was held. Weekly meetings were part of the research methodology to know and understand, at first, what is the imaginary relationship of educators concerning cinema, seeking their concepts regarding its practice in the classroom. At the meetings, immersion exercises were performed in the aspects of sound, visual/photographic experience and the silences as a subjective narrative device. In the next step, photographs of Sebastião Salgado and excerpts from the feature films Lavoura Arcaica and O Som ao Redor were used as an aesthetic awareness device. Lastly, an analysis was performed to understand how this process impacted the teachers’ training. As a theoretical contribution, the studies of Castoriadis (2004, 2006), Fischer (2009), Meira (2001), Estévez (2009), Herman (2005), Oliveira (2014), Fresquet (2015) were considered, in addition to studies developed by members of the Study and Research Group on Education and the Social Imaginary (GEPEIS). It was possible to verify that according to the choice of films used in the classroom, teachers still carry a limited reading knowledge about Brazilian audiovisual production. Also, during the weekly meetings, based on the immersion held in the aesthetics aspects of the films, it provided a greater enjoyment to teachers, impelling them, in the final stage, to experiment with audiovisual creation, which showed that, despite all the difficulties faced in public education, they are confident in the educational possibilities of cinema.